Reinterpretation of the Meaning of Qaulan KarÄman: : An Analysis of Q.S. Al-Israâ€™ (17): 23 Using the MaÊ¿na cum MaghzÄ Approach - Dina Awalia; Umi Masruroh; Jainah; Rusdeana; Akhmad Dasuki; Muhammad Valentino Saputra; Nismah Saâ€™adah (Universitas Islam Negeri Madura, 2026)
The development of digital communication technology has transformed interactions between children and parents, raising the question of how Islamic ethical principles, particularly the concept of qaulan karÄman can be reinterpreted and applied in the context of digital communication. This study examines the meaning of qaulan karÄman in QS. Al-Isra' verse 23 using the maÊ¿na cum maghzÄ approach, emphasizing understanding of the verse based on its historical meaning (maÊ¿na) and its moral and social significance (maghzÄ). A qualitative hermeneutic method was employed, with primary data from the Qur'an and classical and contemporary tafsir, and secondary data from literature on digital communication and family ethics. The analysis reveals that qaulan karÄman refers not only to gentle, polite, and respectful speech but also to moral and social objectives, including maintaining parents' dignity, honor, and emotional well-being. The findings indicate that these principles can be applied in digital communication through text messages, chats, or social media, with attention to word choice, timing, emotional expression, and supportive messages. Challenges in digital communication, such as tonal misinterpretation without verbal cues, risks of conflict from delayed messages, and cultural gaps between generations are also discussed. In conclusion, the reinterpretation of qaulan karÄman provides a framework for ethical, harmonious, and empathetic digital communication, affirming that qurâ€™anic values remain relevant and applicable in modern contexts.